Aortic valve repair versus mechanical valve replacement for root aneurysm: the CAVIAAR multicentric study. (18th May 2022) - Lansac, Emmanuel; Di Centa, Isabelle; Danial, Pichoy; Bouchot, Olivier; Arnaud-Crozat, Eric; Hacini, Rachid; Doguet, Fabien; Demaria, Roland; Verhoye, Jean Philippe; Jouan, Jerome; Chatel, Didier; Lopez, Stephane; et al.
Abstract: OBJECTIVES: Despite growing evidence that aortic valve repair improves long-term patient outcomes and quality of life, aortic valves are mostly replaced. We evaluate the effect of aortic valve repair versus replacement in patients with dystrophic aortic root aneurysm up to 4 years. METHODS: The multicentric CAVIAAR (Conservation Aortique Valvulaire dans les Insuffisances Aortiques et les Anévrismes de la Racine aortique) prospective cohort study enrolled 261 patients: 130 underwent standardized aortic valve repair (REPAIR) consisting of remodelling root repair with expansible aortic ring annuloplasty, and 131 received mechanical composite valve and graft replacement (REPLACE). Primary outcome was a composite criterion of mortality, reoperation, thromboembolic or major bleeding events, endocarditis or operating site infections, pacemaker implantation and heart failure, analysed with propensity score-weighted Cox model analysis. Secondary outcomes included major adverse valve-related events and components of primary outcome. RESULTS: The mean age was 56.1 years, and valve was bicuspid in 115 patients (44.7%). Up to 4 years, REPAIR did not significantly differ from REPLACE in terms of primary outcome [Hazard Ratio (HR) 0.66 (0.39; 1.12)] but showed significantly less valve-related deaths (HR 0.09 [0.02; 0.34]) and major bleeding events (HR 0.37 [0.16; 0.85]) without an increased risk of valve-related reoperation (HR 2.10 [0.64; 6.96]). When accounting for the occurrence of multiple events in a single patient, the REPAIR group had half the occurrence of major adverse valve-related events (HR 0.51 [0.31; 0.86]). CONCLUSIONS: Although the primary outcome did not significantly differ between the REPAIR and REPLACE groups, the trend is in favour of REPAIR by a significant reduction of valve-related deaths and major bleeding events. Long-term follow-up beyond 4 years is needed to confirm these findings. Abstract : Aortic valve repair is now recognized as a good alternative to prosthetic valve replacement with low rate of valve-related events and an improved quality of life compared to valve replacement in monocentric studies [1–4].